The classical D1 dopamine receptor antagonist SCH23390 is a functional sigma-1 receptor allosteric modulator - Zhang Gu-fang; Zhu Kai-lian; Li Qi; Zhang Yue; Waddington John L.; Du Xiang-dong; Zhen Xue-chu (Acta Pharmacologica Sinica, 2024)
SCH23390 is a widely used D1 dopamine receptor (D1R) antagonist that also elicits some D1R-independent effects. We previously found that the benzazepine, SKF83959, an analog of SCH23390, produces positive allosteric modulation of the Sigma-1 receptor (Sig1R). SCH23390 does not bind to the orthodoxic site of Sig1R but enhances the binding of 3H (+)-pentazocine to Sig1R. In this study, we investigated whether SCH23390 functions as an allosteric modulator of Sig1R. We detected increased Sig1R dissociation from binding immunoglobulin protein (BiP) and translocation of Sig1R to the plasma membrane in response to SCH23390 in transfected HEK293T and SH-SY5Y cells, respectively. Activation of Sig1R by SCH23390 was further confirmed by inhibition of GSK3β activity in a time- and dose-dependent manner; this effect was blocked by pretreatment with the Sig1R antagonist, BD1047, and by knockdown of Sig1R. SCH23390 also inhibited GSK3β in wild-type mice but not in Sig1R knockout mice. Finally, we showed that SCH23390 allosterically modulated the effect of the Sig1R agonist SKF10047 on inhibition of GSK3β. This positive allosteric effect of SCH23390 was further confirmed via promotion of neuronal protection afforded by SKF10047 in primary cortical neurons challenged with MPP+. These results provide the first evidence that SCH23390 elicits functional allosteric modulation of Sig1R. Our findings not only reveal novel pharmacological effects of SCH23390 but also indicate a potential mechanism for SCH23390-mediated D1R-independent effects. Therefore, attention should be paid to these Sig1R-mediated effects when explaining pharmacological responses to SCH23390.